EPIDEMIOLOGICAL RISK FACTORS AND COMPOSITION OF URINARY STONES IN RIYADH SAUDI ARABIA - Khan, Abdus Salam; Rai, Manzoor Ellahi; pur, Ganda; Pervaiz, Ayesha; Shah, Arif Hussain; Hussain, Abdallah Aba; Siddiq, Muhammad (Journal of Ayub Medical College Abbottabad, 2004)
Background: The purpose of this study was to perform the chemical analysis of stones to know the pattern of biochemical composition of stones and to determine epidemiological risk factors for stone formation in Riyadh Saudi Arabia. Methods: 307 renal stones were analyzed during one year period from September 2000 to August 2001. These stones were sent to central lab Riyadh for analysis from different hospitals attached to this region. The stones were analyzed by semiquantitative method. The kits supplied by Maascia Bruneli SPA. (Italy) was used for chemical analysis of stones. The powered stones and standards both were analyzed for uric acid, cystine, oxalate, carbonate, phosphate, ammonia, calcium and magnesium contents. Results: Male to female ratio was 5:1. The stone frequency was 2.5 times more in Saudis as compared to non-Saudis. Maximum number of stones were analyzed in peak summer months. Calcium oxalate stones were the commonest followed by uric acid and phosphate stones. No cystine stone was found in the series analyzed. Conclusion: From the study of epidemiological factors it seems that the Saudis are more prone to development of stones. A clear stone season seems to exist in the area corresponding to the summer months. The relative increased frequency of stones in the region indicates that nutritional, environmental and genetic factors play a role in the occurrence of stones. Keywords: urinary stones, composition, epidemiology